2015
DOI: 10.1039/c4tb02051k
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-functionalized copolymer micelles as a drug delivery system in 2D and 3D models of breast cancer

Abstract: Histamine functionalized block copolymers based on poly(allyl glycidyl ether)-b-poly(ethylene oxide) (PAGE-b-PEO) were prepared with different ratios of histamine and octyl or benzyl groups using UV-initiated thiol-ene click chemistry. At neutral pH, the histamine units are uncharged and hydrophobic, while in acidic environments, such as in the endosome, lysosomes, or extracellular sites of tumours, the histamine groups are positively charged and hydrophilic. pH responsible polymer drug delivery systems is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
(127 reference statements)
1
22
0
Order By: Relevance
“…In cancer therapy, it is known that drug-loaded DDS cannot compete with free drugs because drug release within DDS cannot reach 100% and, as a result, the cell viability of DDS is higher than that of free drugs ( 35 , 36 ). However, when applied in vivo , DDS show more advantages than free drugs as they can be modified to more specifically target tumor tissue and increase local drug concentration as well as avoid side effects ( 37 , 38 ). However, the co-delivery of DTX and TDD exerted much more potent anti-cancer effects than either single drug-loaded formulation or free drugs at all the adopted drug concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In cancer therapy, it is known that drug-loaded DDS cannot compete with free drugs because drug release within DDS cannot reach 100% and, as a result, the cell viability of DDS is higher than that of free drugs ( 35 , 36 ). However, when applied in vivo , DDS show more advantages than free drugs as they can be modified to more specifically target tumor tissue and increase local drug concentration as well as avoid side effects ( 37 , 38 ). However, the co-delivery of DTX and TDD exerted much more potent anti-cancer effects than either single drug-loaded formulation or free drugs at all the adopted drug concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…61 In addition, PAGE is an analog of poly(ethylene oxide) with a high density of allyl groups along its backbone that can be readily functionalized. [62][63][64] This is particularly important because it opens up the possibility for the divergent preparation of a variety of BCPs for any targeted application with no need for protection-deprotection procedures. In fact, it has been shown that the allyl groups on PAGE backbone can be readily modified with biologically-relevant molecules of interest via thiol-ene radical coupling.…”
Section: Synthesis and Characterization Of Amphiphilicmentioning
confidence: 99%
“…It was found that the histamine functionality facilitated endosomal escape and enhanced doxorubicin targeting to the mitochondria as compared to free Dox. [128] Chen et al have prepared nanoparticles that were composed of a quaternary ammonium-functionalized chitosan derivative and a chitosan derivative modified with N-glycyrrhetinic acid moieties via Schiff base PEG spacer. These nanoparticles were used for the delivery of brucine.…”
Section: Mitochondrial Deliverymentioning
confidence: 99%
“…Positive charges [103] Linear polymers [24,[104][105][106][107]113,[116][117][118][119][120][121][122][123][124] Branched polymers [24,106,113,115,116,[125][126][127] Dendrimers [108][109][110][111][112]116] Charge-reversal [103] Linear polymers [11,22,129,132,133,135] Micelles [128,130,131,134,236] Dendrimers [136] Volumetric expansion Nanoparticles [237] Membranedisrupting peptides Endosomes/ lysosomes [102] N-terminal HA2 peptide derivative Linear polymers [21] INF-7 peptide Linear polymers [137,138] GALA PEGylated liposomes …”
Section: Endosomes/ Lysosomesmentioning
confidence: 99%
See 1 more Smart Citation